2020
DOI: 10.2147/idr.s237793
|View full text |Cite
|
Sign up to set email alerts
|

<p>First Report of OXA-181-Producing <em>Klebsiella pneumoniae</em> in China</p>

Abstract: We present here the first report of an OXA-181-producing Klebsiella pneumoniae isolated from the fecal specimen of a patient in China. The OXA-181-encoding gene bla OXA-181 was located on a 51 kb IncX3-type plasmid. Conjugation assay and wholegenome sequencing analysis revealed that this transferrable plasmid in the K. pneumoniae isolate might have originated from Escherichia coli and have the potential to mediate the spread of bla OXA-181 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…in clinical K. pneumoniae and C. koseri from Croatia 152 . IncX 3 was associated with bla OXA‐181 in clinical K. pneumoniae, E. coli , or E. cloacae in studies from Angola, 76 Egypt, 73 and São Tomé and Príncipe; 75 bla NDM‐5 was carried on IncX 3 in E. coli in South Africa; 68 and similar findings in Mali showed E. coli harbored bla NDM‐5 , 131 in agreement with some Chinese studies that confirmed the existence of bla OXA‐181 or bla NDM‐5 on IncX 3 plasmids in K. pneumoniae or E. coli isolates 153–155 …”
Section: Carbapenemase‐associated Mgessupporting
confidence: 83%
“…in clinical K. pneumoniae and C. koseri from Croatia 152 . IncX 3 was associated with bla OXA‐181 in clinical K. pneumoniae, E. coli , or E. cloacae in studies from Angola, 76 Egypt, 73 and São Tomé and Príncipe; 75 bla NDM‐5 was carried on IncX 3 in E. coli in South Africa; 68 and similar findings in Mali showed E. coli harbored bla NDM‐5 , 131 in agreement with some Chinese studies that confirmed the existence of bla OXA‐181 or bla NDM‐5 on IncX 3 plasmids in K. pneumoniae or E. coli isolates 153–155 …”
Section: Carbapenemase‐associated Mgessupporting
confidence: 83%
“…The OXA-181-encoding gene was first reported in 2007 and was subsequently identified in several countries, including its recent detection in Ghana [ 15 , 16 , 33 ]. It is mainly found in E. coli and K. pneumoniae strains with an increasing prevalence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OXA-181-encoding gene was first reported in 2007 and was subsequently identified in several countries, including its recent detection in Ghana [ 15 , 16 , 33 ]. It is mainly found in E. coli and K. pneumoniae strains with an increasing prevalence [ 33 ]. The IncX3 plasmid pEC187_2-OXA-181 harbouring bla OXA-181 showed the same nucleotide identity as 17 other plasmids from 9 different countries (Czech Republic, Denmark, Myanmar, Lebanon, Japan, United Arab Emirates, United Kingdom, Switzerland and United States).…”
Section: Discussionmentioning
confidence: 99%
“…So far, several studies have reported plasmids carrying bla OXA-181 with different replicons, such as IncX3, IncA/C, ColE, IncT, IncN, IncFIIK and ColKP3 (Villa et al, 2013;Naha et al, 2021). But the most common plasmid in China is the IncX3 type which has a similar genetic environment to others (Liu et al, 2020). The similar bla OXA-181 bearing IncX3 plasmid further highlights the role of IncX3type plasmid as an irreplaceable vector of ARGs (Santos Tufic-Garutti et al, 2022).…”
Section: Discussionmentioning
confidence: 98%